Media Interaktif berbasis Adobe Flash pada Pembelajaran di Sekolah Dasar - Utomo, Hanif Satrio (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
The use of media in classroom learning is now verry much needed. This analysis aims to find out whether Adobe Flash media in elementary school learning has an effect on elementary school learning. This research also wants to look at the characteristics of Adobe Flash media. This research method uses qualitative research method. This method focuses on deeper observastions. Based on the results of this research, it shows that the use of interactive media based on Adobe Flash is in accordance with the characteristics of Adobe Flash and the learning conditions that emerge get a percentage of 90% which shows positive results for students and for educators in achieving the desired learning. In conclusion, it is hope that this media will become an alternative medium for achieving fun and good learning and it is hoped that every capable teacher and young teacher can carry out learning by not only using books but using additional media that are in line with current technological advances. So that learning becomes interesting and of course you don’t get bored in the class.